Language, Power, and Ideology on Joe Biden's Speech: A Critical Discourse Analysis - Amanda, Rifa Alya; Handayani, Tuty (Institut Agama Islam Negeri Ponorogo, 2024)
This study examines Joe Biden's speech delivered during his visit to a Steamfitters training facility in Virginia by using Critical Discourse Analysis (CDA). This research aims to analyze the substance of Biden's speech in the economic sector by examining the text and sociocultural context, using qualitative research methodology by applying Norman Fairclough's framework of critical discourse analysis. Fairclough's Critical Discourse Analysis (CDA) comprises three fundamental components: texts, discourse practices, and sociocultural practices. By using this theory, it is clear that Biden's diction includes specific word categorization through modality, repetition, and the use of first-person singular pronouns to show his full authority and power and to criticize Congressional Republicans. In addition, Biden's speech also served as a political speech and strategic means to rally citizens' support in the United States.